Pengembangan Bahan Ajar Inovatif dan Interaktif Melalui Pendekatan Saintifik Pada Pengajaran Termokimia - Erdiana Gultom; Manihar Situmorang; Ramlan Silaban (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. This study aims to obtain innovative and interactive teaching materials integrated scientific approach and involves a web-based information technology. This type of research, including research and development (research and development). Subjects were subject thermochemical teaching materials. Meanwhile, the sample used in this study consisted of 20 students majoring in chemistry chemistry education courses of the Faculty of Mathematics and Natural Sciences, University of Medan and 3 lecturers basic courses at the State University of Medan. Selection of the sample using purposive sampling technique. The results of chemical analysis of teaching materials common is that the teaching materials are quite valid, but need to be developed from various aspects. Teaching materials that have been developed validated by expert validator. Assessment is done based on a standard questionnaire BSNP (National Education Standards Agency). Based on research data obtained an average of 23 respondents think that consists of 3 professors and 20 students on the quality of teaching materials developed 3.49  belonging to the criteria of a very valid means of the development of teaching materials is very feasible for use in learning. Elaboration of the overall average respondent to the quality of teaching materials developed are the average results of the assessment of General Chemistry lecturers in the amount of 3.66 and an average student assessment results Chemistry education that is equal to 3.31. Keywords: research and development (R&D), thermochemical, scientific approach